Annual Population Dynamics of Copepods and its Correlation with Water Parameters in Fish Ponds of Ludhiana District, Punjab - Jamwal, Shreya; Kocher, Devinder Kaur (Asian Journal of Biological and Life Sciences, 2017)
Zooplankton are the important part of aquatic food chain and the nutritious food for fish. Some zooplankton like cyclopoid copepods are the voracious predators of earlier instar mosquito larvae. In present study, copepod density as well as physico-chemical parameters like temperature, transparency, pH, electrical conductivity, total dissolved solids, dissolved oxygen, alkalinity and total hardness were recorded from selected three fish ponds of Ludhiana district of Punjab (India) from January-December 2014. Results showed the maximum copepod density (copepods L-1) during March at GADVASU (2740.68 L-1) and during April at Pandori (1231.60 L-1) and Galib Kalan (2779.63 L ) fish ponds. From the collected zooplankton pool, annual count showed high population of mature copepods in comparison to immature one (including nauplii and copepodids) and from the mature population, cyclopoids were the predominant (60 to 79.33%) type of copepods found in the selected fish ponds. A significant negative correlation (r = -.603 at p<0.05) was observed between the copepod population and temperature at GADVASU fish pond and other two fish ponds, this relation was statistically non-significant. While rest of the studied water parameters showed statistically non-significant correlation with copepod ○ population. The temperature favourable for high population of copepods was found to range from 20-27 C.
Keywords: Cyclopoids; pH; Physico-Chemical parameters; Predators; Temperature; Zooplankton